Organisational Commitment in UK Organisations: Do Cultural Backgrounds and Brexit Matter? - Wang, Mengyuan (2017)
The research investigates whether cultural backgrounds and Brexit are determinants of organisational commitment in United Kingdom as the UK is a country with a multicultural working environment. Power distance, individualism/collectivism, work-life balance and language have all been tested in the research as cultural variables to examine participants’ difference on cultural background and whether there are differences on their organisational commitment level within the UK companies. The relationship between Brexit and organisational commitment have also all been tested in the research by analysing how EU employees value Brexit in regard to working in the UK and whether EU employees have different levels of organisational commitment. The topic is related to the current working environment in the UK as the cultural background of UK employees are more diverse than before. The topic is also relevant in UK’s current situation in the Europe as leaving the EU is an imperative and countless new problems are expected to arise including the issue of whether to continue working in the UK or not. The aim of this study is to help UK organisations to find solutions of increasing employees’ organisational commitment and to provide advice on how to manage EU employees during the post Brexit time.